Is Educating Girls the Best Investment for South Asia? Association Between Female Education and Fertility Choices in South Asia: A Systematic Review of the Literature - Sheikh, Saba M.; Loney, Tom (Frontiers in Public Health, 2018)
Background: Universal education is a key strategy to enhance the well-being of individuals and improve the economic and social development of societies. A large proportion of school-aged girls in developing countries are not attending schools. Approximately one-third of South Asian girls do not attend school and in some regions only one in four girls attend primary school. Eliminating gender disparities in school attendance may lead to improvements in female education and reproductive health. Objectives: To conduct a systematic review of the available data from international organizations and regional registries to explore the association between female education and fertility choices in South Asia. Methods: Systematic review and synthesis of secondary data. Data sources: MEDLINE, Embase, Google Scholar, World Health Organization, World Bank, United Nations Population Fund, Millennium Development Goals, Institute of Health Management, World Fact book, United States Centers for Disease Control and Prevention and regional registries were searched for papers published between 1970 and October 2016 and the included papers contained data from 1960. Study eligibility criteria and data abstraction process: Studies were included if they contained data on (i) female education and/or literacy levels in South Asia; and (ii) fertility behavior in South Asian females. Quality of the included studies and extracted data were assessed by two independent reviewers. Results: According to the World Bank report in 2016, the female literacy rate in South Asia has increased from 45.5% in 2000 to 57.0% in 2010 while a decreased trend of total fertility rate (i.e., number of children born per woman) was observed from 6.0 in 1960 to 2.6 in 2014. Limitations: Only studies in English were included. Conclusion: A negative relationship seems to exist between levels of literacy and total fertility rates in South Asian females which if further improved may contribute to longer-term improvements in maternal and child health.